Effects of laser surface modification on stainless steel 316L thin annular discs under radial and cartesian scans. (January 2023) - González, Matías; Ramos-Grez, Jorge A.; Jeria, Ignacio; Guerra, Carolina; Solis, Roberto; Carvajal, Linton
Highlights: An empirically study the Laser Surface Melting (LSM) technique on 316L stainless steel annular discs was done to evaluate the influence of laser scanning pattern on the results of the laser treatment. A complete characterization of laser treatment on 316L stainless steel annular discs was done in annular discs under two scanning pattern schemes: cartesian and polar. Under the same conditions, variation of the scanning pattern produces a meaningful change in the stress state of the specimen and its deformation after treatment. LSM treatment increased crystallite size and decreased dislocation density, it introduced a state of compression, a slight hardening in the melted layer, and a decrease in toughness. This knowledge can be used to encourage the use the use of polar laser scanning patterns in this field. Abstract: Lasers direct use on metals allows treatment of localized surfaces, without affecting nearby material or the body of the piece. Depending on the expected result, laser surface treatments are classified into hardening, texturing, alloying, coating, and melting. Using the latter is possible to modify the microstructure, dissolve precipitates, and increase hardness and wear resistance, among other applications depending on the material and the parameters used. In this work, it is proposed to empirically study the Laser Surface Melting (LSM) technique on 316L stainless steel annular discs, to evaluate the influence of laser scanning pattern on the results of the laser treatment. The considered scanning patterns correspond to a Cartesian, the most used pattern in the LSM process, also known as "zigzag", and a Radial pattern, previously proposed in Additive Manufacturing research, which moves the laser in a cylindrical way. The main contribution of this work is to introduce the variable of the scanning pattern in LSM studies, besides, generating a complete characterization of laser treatment on 316L stainless steel annular discs. The results show that, under the same conditions, the variation of the scanning pattern produces a meaningful change in the stress state of the specimen and its deformation after treatment. The main results of LSM treatment were an increase in crystallite size and a decrease in dislocation density, a state of compression, a slight hardening in the melted layer, and a decrease in toughness. This knowledge can be used to encourage new scanning patterns in this field.